Internet-based group compassion-focused therapy for Swedish young people with stress, anxiety and depression: a pilot waitlist randomized controlled trial - Vestin, Magnus; Wallin, Linda; Naesström, Matilda; Blomqvist, Ida; Svedin, Carl Göran; Beaumont, Elaine; Jokinen, Jussi; Dennhag, Inga (Frontiers in Psychology, 2025)
IntroductionCompassion-focused therapy (CFT) has shown promising outcomes for young people, but research on CFT for this population remains limited. This study aims to evaluate the feasibility and acceptability of a seven-session, therapist-led, internet-based group CFT for young people, and to investigate its preliminary effects.MethodsA two-arm pilot randomized controlled trial (RCT) was conducted. The study included 42 participants (aged 15–20), experiencing mild to moderate stress, anxiety, or depression, most of whom (90%) were female. In the intervention group, 22 participants were included in the intention-to-treat (ITT) analysis. The trial was registered at ClinicalTrials.gov (NCT05448014).ResultsThe intervention group had low attrition and moderate attendance, with 77% completing four or more modules. No adverse events were reported, and participants generally expressed satisfaction with the intervention. Linear regression models showed preliminary between-group differences in two variables. Depressive symptoms increased post-intervention for individuals in the intervention group compared to the waitlist (WL) group (p = 0.002). Self-compassion improved in the intervention group (p = 0.023). These patterns were consistent among participants who completed more than two sessions. Within-group analyses indicated moderate, significant improvements in stress, self-compassion and compassion from others.DiscussionThese preliminary results suggest that CFT is feasible and acceptable and may offer benefits for young people, particularly by enhancing self-compassion and compassion for others. The observed increase in depressive symptoms in the intervention group, despite improvements in self-compassion, warrants further investigation. Larger studies are needed to confirm these preliminary results and to better understand the underlying mechanisms.